Synthetic Strategies for Accessing Dibenzophosphole Scaffolds - Hattori, Hiroyuki; Ishida, Kento; Sakai, Norio (Synthesis, 2023)
Dibenzophospholes, phosphorus-containing π-conjugated cyclic compounds, have attracted considerable attention because of their potential applications in various functional materials such as those required for organic electroluminescent devices. Moreover, their synthetic methods have been widely developed. This review summarizes the construction strategies of dibenzophosphole scaffolds, including those developed recently.1 Introduction2 Construction of a Phosphole Skeleton Using Aryl Compounds2.1 [4+1] Cyclization between Biaryl Derivatives and P1 Units2.2 Intramolecular P–C Bond Formation of Biarylphosphines2.3 Intramolecular C–C Bond Formation of Diarylphosphines2.4 [3+2] Cyclization between Arylphosphines and Arenes3 Fused-Benzene Ring Formation4 Successive Phosphole Skeleton and Fused-Benzene Ring Formation5 Conclusions
Keywords: dibenzophospholes; phosphorus; π-conjugated phosphacycle; cyclization; synthetic method